The role of trust in social commerce site in purchasing behavior on TikTok shop Indonesia - Burhanudin , Burhanudin; Puspita, Hilda Marsya (Universitas Tarumanagara, 2023)
Social commerce has developed as something new trend that utilizes social media to influence consumer purchasing behavior. This article aims to investigate the direct influence of informational support and emotional support on purchasing behavior as well as its indirect influence through trust in social commerce sites. A survey was conducted among a sample of 263 consumers who have engaged in social commerce through TikTok Shop. The collected data was analyzed using the structural equation modeling technique. Based on the research findings, it was revealed informational support and emotional support has direct influences on purchasing behavior and indirectly through trust in social commerce site. The findings imply that establishing trust is essential for driving consumer behavior in the context of social commerce. Moreover, the presence of social commerce platforms motivates marketers to leverage social media as a more effective marketing tool to build consumer trust and shape purchasing behavior. These findings highlight the significance of trust-building strategies and the potential of social commerce in influencing consumer decision-making processes. Social commerce telah berkembang sebagai tren baru yang memanfaatkan media sosial untuk memengaruhi perilaku pembelian konsumen. Artikel ini bertujuan untuk menyelidiki pengaruh langsung informational support dan emotional support terhadap purchasing behavior serta pengaruh tidak langsungnya melalui trust in social commerce site. Sebuah survei dilakukan terhadap 263 sampel konsumen yang telah terlibat dalam trust in social commerce site melalui TikTok Shop. Data yang terkumpul dianalisis dengan menggunakan teknik model persamaan struktural. Penelitian ini menemukan informational support dan emotional support memiliki pengaruh langsung terhadap purchasing behavior dan secara tidak langsung melalui trust in social commerce site. Temuan ini menunjukkan bahwa membangun kepercayaan sangat penting untuk mendorong perilaku konsumen dalam konteks social commerce. Selain itu, kehadiran platform social commerce memotivasi pemasar untuk memanfaatkan media sosial sebagai alat pemasaran yang lebih efektif untuk membangun kepercayaan konsumen dan membentuk perilaku pembelian. Temuan ini menyoroti pentingnya strategi membangun kepercayaan dan potensi social commerce dalam memengaruhi proses pengambilan keputusan konsumen.